Minority entrepreneurship - Bates, Timothy (Foundations and trends in entrepreneurship, 2011)
In the field of minority entrepreneurship, sociologists and economists have written most of the influential studies, yet these groups typically ask different questions and base their analysis on different assumptions. The literature predictably lacks a single unifying focus and is quite diverse regarding issues explored and methodological approaches employed. Differing approaches and their outcomes are summarized and critically probed in this review. My intent is to illuminate strengths and weaknesses -- along with patterns of common findings -- in this voluminous literature. Minority-owned businesses are collectively reflections of evolving constraints and opportunities operating in broader society. Minorities seeking to create viable business ventures have traditionally faced higher barriers than whites as they sought to exploit market opportunities, raise financing, and penetrate mainstream networks. Entrepreneurial dynamics are clarified by focusing upon specific contexts in which firms are being shaped by prevailing opportunity structures. Progress has been noteworthy overall for minority-owned businesses, in part because barriers impeding their collective development have been gradually declining